Faktor-Faktor yang Berhubungan dengan Konsumsi Fast Food pada Remaja Obesitas di SMA Theresiana 1 Semarang Tahun 2017 - Liyana Putri Afifah; Suyatno Suyatno; Ronny Aruben; Apoina Kartini (Jurnal Kesehatan Masyarakat (Undip), 2017)
Obesity or commonly known as overweight is a quite disturbing problem among teenagers. Fast food is a fast serving food with big portion, and heavy energy food with high calories and fat. The purpose of the research was to analyze factors related with fast food consumption in adolescent obesity in Theresiana 1 Senior High School Semarang 2017. This research was using quantitaive study method with cross sectional design. Research population were adolescent obesity in XII grade with the total of 35 people. Samples in this research were 35 adolescent obesity who met the inclusion criteria. Sampling technique was using total sampling. Data was analyzed using Chi Square test. The results showed that respondent’s knowledge about fast food was classified as adequate (48,6%). Respondent’s attitude about fast food consumption was classified as adequate (42,9%). Parents income was classified as very high (65,7%). Respondent’s pocket money was classified as high (82,9%). Friends with the same age was classified as not influence (51,4%). Mass media was classified as not influence (54,3%). Statistical results showed that there were no correlations of knowledge (p=0,166), attitude (p=0,677), parents income (p=0,668), pocket money (p= 0,975), friends with the same age (p= 0,145), mass media (p= 0,982) with fast food consumption. This research recommended adolescent obesity to reduce fast food consumption and chose the balance nutrition food in school canteen or other restaurants which suitable with students daily energy needs.